Landing your dream job - J. Michael Farr (Thomson Delmar Learning, 2006)
Landing Your Dream Job is the most thorough and user-friendly workbook on self-directed career planning, job search, and career survival available. It covers all the major topics, yet is fun to read and easy to use. It is results-oriented, and chock full of interactive activities. Not only is the workbook full of charts, checklists, worksheets, and in-the-book-activities, there are many sample resumes, including scannable resumes. CD with Resume Generator and Printable Datakeeper further aid students in landing their dream job